INSTRUMENT DEVELOPMENT OF HIGHER ORDER THINKING SKILL IN MATHEMATICS INSTRUCTIONAL ON SENIOR HIGH SCHOOL - Benidiktus Tanujaya (LPPM Universitas Negeri Jakarta, 2015)
The purpose of this research was to develop an instrument that can be used to measure higher-order thinking skills (HOTS) in mathematics instructional of high school students. This research was conducted using a standard procedure of instrument development, from the development of conceptual definition, development of operational definitions, determination constructs, dimensions, and indicators, to the preparation of blue print, item preparation, expert validation, and testing. Data results from trials be analyzed using factor analysis and analysis of structural equation modeling (SEM). The data analysis shows that there are 9 factors HOTS that construct the instrument with good validity and reliability. This instrument classifies high school students in the five categories of HOTS ability. HOTS grouping results can be used by various interested institutions to evaluate the instructional of mathematics. These evaluations are used to determine the success of student learning and the success of teachers' teaching.